The Coincidence of 3 Different Rare Coronary Artery Anomalies in an Adult Patient With Untreated Kawasaki Disease: Case Report. Issue 12 (March 2016) - Jiang, Xin; Liao, Shusheng; Xiong, Bin; Zheng, Lei; Zhu, Huijia; Zhu, Xuelian; Ni, Xianda; Zheng, Xiangwu; Chen, Bin
Abstract : Abstract: The coincidence of 3 different rare coronary artery anomalies is extremely rare, and has not been reported so far. We report multiple imaging findings of a giant coronary artery aneurysm, which has a fistulous connection to the right ventricle associated with anomalous origin of the anterior descending coronary artery from the right coronary artery in a 67-year-old woman who suffered with a 20-year history of progressively chest distress on exertion and a history of untreated Kawasaki disease in her childhood. The patient received surgical treatment. The aneurysm was resected and openings at both ends being oversewn. And the fistula was also closed directly. She recovered and discharged uneventfully. The coincidence of 3 different rare coronary artery anomalies in adult patient with untreated Kawasaki disease is a rare and complicated condition, in which surgical treatment is recommended.